Phosphor
A novel phosphor with the formula Na2Ba9-xSi20O50:Eu^2+ addresses the need for high color reproducibility and heat resistance by emitting light in the 530 to 550 nm range with improved spectral characteristics.
Patent Information
- Application Number
- JP2023144115
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-18
AI Technical Summary
There is a growing need for new phosphors that offer high color reproducibility and heat resistance as existing phosphors are not sufficient to meet these expanding design requirements.
The development of a novel phosphor with the formula Na2Ba9-xSi20O50:Eu^2+, which has a monoclinic crystal structure and specific lattice constants, and emits light in the wavelength range of 530 to 550 nm with a half-width of less than 135 nm.
This novel phosphor provides enhanced color reproducibility and heat resistance, expanding design options for applications such as light-emitting diodes and display devices.
Smart Images

Figure 2025037293000002 
Figure 2025037293000003 
Figure 2025037293000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to phosphors. [Background technology]
[0002] Phosphors are used in a variety of products, such as vacuum-fluorescent displays (VFDs), field emission displays (FRDs), surface-conduction electron-emitter displays (SEMs), plasma display panels (PDPs), cathode-ray tubes (CRTs), liquid-crystal display backlights, and light-emitting diodes (LEDs).
[0003] As phosphors, various phosphors are known, such as phosphors in which an activator element is dissolved in a nitride such as β-SiAlON or CASN. In addition, Patent Document 1 discloses Na5Al3F 14 For Mn 4+ Patent Document 2 discloses a red phosphor containing Sr 6x (Si,Al) 27-12x (O,N) 31-6x Li 3y , where 0.4≦x≦0.8, 0≦y≦0.35, and Sr3Si 12.432 Al 8.568 O 1.608 N 26.392 Li 0.96 A phosphor containing an inorganic compound having as a host crystal a crystal having the same crystal structure as that of the above-mentioned compound is disclosed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Laid-Open No. 2019-215451 [Patent Document 2] International Publication No. 2022 / 244523 [Summary of the Invention] [Problems to be Solved by the Invention]
[0005] With the expansion of the region where phosphors are used, various new phosphors are demanded from the viewpoint of expanding design options according to required characteristics such as high color reproducibility and heat resistance.
[0006] The present disclosure aims to provide a novel phosphor. [Means for Solving the Problems]
[0007] The present disclosure provides the following [1] to [8].[[]END]]
[0008] [1] A host crystal having the same crystal structure as Na2Ba9Si 20 O 50 and, as an activating element, Eu 2+ A phosphor having the same. [2] The phosphor according to [1], having an emission peak in the wavelength range of 530 to 550 nm in the fluorescence spectrum obtained when irradiated with light having a wavelength of 378 nm. [3] The phosphor according to [2], wherein the full width at half maximum of the emission peak is less than 135 nm. [4] The phosphor according to any one of [1] to [3], represented by the general formula Na2Ba 9-x Si 20 O 50 :Eu x [wherein x is a numerical value satisfying 0 < x < 9].[[]END]] [5] The phosphor according to any one of [1] to [4], wherein the host crystal belongs to the monoclinic system and has a crystal symmetry of space group C12 / m1(12). [6] The unit cell volume calculated from the lattice constants of the host crystal measured by X-ray diffraction is 2.1 to 2.8 nm 3The phosphor according to any one of [1] to [5], [7] The lattice constants a, b, and c of the host crystal measured by X-ray diffraction are respectively: a = 3.91 ± 0.05 nm, b = 0.77 ± 0.05 nm, c = 0.82 ± 0.05 nm, The phosphor according to any one of [1] to [6], [8] The axial angles α, β, and γ in the unit cell of the host crystal measured by X-ray diffraction are, respectively: α=90°, 96°≦β≦98°, γ=90°, The phosphor according to any one of [1] to [7], Effect of the Invention
[0009] According to the present disclosure, a novel phosphor can be provided. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a light emitting device. [Diagram 2] FIG. 2 shows the emission spectrum of the phosphor prepared in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, embodiments of the present disclosure will be described. However, the following embodiments are merely examples for explaining the present disclosure, and are not intended to limit the present disclosure to the following contents.
[0012] Unless otherwise specified, the materials exemplified in this specification can be used alone or in combination of two or more. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified.
[0013] The phosphor according to an embodiment of the present disclosure is Na2Ba9Si 20 O 50 It has a host crystal having the same crystal structure as that of, and Eu as an activating element 2+ And. The activating element may be substitutionally solid-solved for a part of the elements constituting the host crystal. The phosphor has the general formula Na2Ba 9-x Si 20 O 50 :Eu x [In the general formula, x is a numerical value satisfying 0 < x < 9].
[0014] The constituent elements and ratios of the phosphor can be determined by an ICP emission spectroscopic analysis method using a multi-type ICP emission spectrometer. In addition, since the elemental composition in the phosphor corresponds to the charging ratio of each element when manufacturing the phosphor, the elemental composition of the phosphor can also be estimated from the raw material composition.
[0015] Whether the host crystal has the same crystal structure as Na2Ba9Si 20 O 50 Can be confirmed by performing X-ray diffraction measurement. More specifically, for the host crystal to be measured, X-ray diffraction measurement is performed to obtain the lattice constants a, b, and c, and the axial angles α, β, and γ, and the obtained lattice constants and axial angles are compared with the lattice constants and axial angles of Na2Ba9Si 20 O 50 . The lattice constants and axial angles of Na2Ba9Si 20 O 50 Are a = 3.91 nm, b = 0.77 nm, and c = 0.82 nm, α = 90°, 96° ≤ β ≤ 98°, and γ = 90°, respectively. The lattice constants a, b, and c, and the axial angles α, β, and γ of the host crystal of the phosphor to be measured are such that the lattice constants deviate by ±0.05 nm and the axial angles deviate by ±2° from the lattice constants a, b, and c, and the axial angles α, β, and γ of Na2Ba9Si 20 O 50 Can occur. In addition to the above method, the host crystal is Na2Ba9Si 20 O 50To determine whether the host crystal has the same crystal structure as Na2Ba9Si, a diffraction pattern is obtained by X-ray diffraction measurement. 20 O 50 In the diffraction pattern (graph with the horizontal axis representing the diffraction angle 2θ [unit: °] and the vertical axis representing the diffraction intensity [unit: CPS]) obtained by performing X-ray diffraction measurement on the host crystal to be measured, 20 O 50 It can be judged by the diffraction pattern obtained by X-ray diffraction measurement and whether or not the main peak is observed. 20 O 50 The main peaks in the diffraction pattern obtained by X-ray diffraction measurement of Na2Ba9Si are confirmed at 23.5°, 26.8°, 28.0°, and 32.8°. 20 O 50 The target peaks to be compared with the main peak positions of the diffraction pattern of Na2Ba9Si may deviate by ±0.2° from the above-mentioned main peak positions. 20 O 50 The diffraction pattern obtained by performing powder X-ray diffraction measurement on a host crystal having the same crystal structure as that of has peaks at 23.5±0.2°, 26.8±0.2°, 28.0±0.2°, and 32.8±0.2°. In X-ray diffraction measurement in which a phosphor is used as the measurement object, peaks derived from the host crystal are also observed, so the measurement object may be a phosphor powder or a single particle contained in the powder.
[0016] The host crystal is Na2Ba9Si 20 O 50 The host crystal may be, for example, Na2Ba9Si 20 O 50 etc.
[0017] The host crystal may belong to the monoclinic system and may be a crystal having space group C12 / m1(12) symmetry.
[0018] In this specification, the space group of a crystal is determined by comparing the diffraction pattern of the X-ray diffraction spectrum for the sample to be measured with the diffraction pattern of a crystal group with a defined symmetry.
[0019] The phosphor may be prepared so that the lattice constants a, b, and c of the host crystal measured by X-ray diffraction are within a predetermined range. Here, the lattice constants a, b, and c refer to the a-axis length, b-axis length, and c-axis length of the host crystal, respectively. The lattice constants a, b, and c of the host crystal in the phosphor may be a=3.91±0.05 nm, b=0.77±0.05 nm, and c=0.82±0.05 nm, respectively.
[0020] The phosphor may be prepared so that the axial angles α, β, and γ in the unit cell of the host crystal measured by X-ray diffraction are within a predetermined range. The axial angles α, β, and γ in the phosphor may be α=90°, 96°≦β≦98°, and γ=90°, respectively.
[0021] In the phosphor, the unit lattice volume calculated from the lattice constant of the host crystal measured by X-ray diffraction is 2.1 to 2.8 nm 3 The unit cell volume of the phosphor may be, for example, 2.2 nm 3 Above, 2.3nm 3 or more than 2.4 nm 3 The unit cell volume of the phosphor may be, for example, 2.7 nm 3 Below, 2.6nm 3 Less than or equal to 2.5 nm 3 It may be the following:
[0022] The emission peak wavelength of the above phosphor depends on the amount of Eu in solid solution and the proportion of Eu in the solid solution element. 2+The ratio of the phosphor to the total phosphor may be adjusted. In the fluorescence spectrum obtained when irradiated with light having a wavelength of 378 nm, the phosphor may have an emission peak in the wavelength range of 530 to 550 nm. In the fluorescence spectrum obtained when irradiated with light having a wavelength of 378 nm, the emission peak wavelength having the maximum emission intensity of the phosphor belonging to the wavelength range of 530 to 550 nm may be, for example, 532 nm or more, 535 nm or more, or 540 nm or more. The emission peak wavelength having the maximum emission intensity of the phosphor may be, for example, 549 nm or less, 548 nm or less, or 545 nm or less.
[0023] The phosphor can have a small half-width of an emission peak having a maximum emission intensity in a wavelength range of 530 to 550 nm in a fluorescence spectrum obtained when irradiated with light having a wavelength of 378 nm. The upper limit of the half-width of the emission peak may be, for example, less than 135 nm, 134 nm or less, or 133 nm or less. By setting the upper limit of the half-width of the emission peak within the above range, a phosphor having a higher emission intensity can be obtained. The lower limit of the half-width of the emission peak is not particularly limited, but may be, for example, 30 nm or more, or 40 nm or more.
[0024] In this specification, the wavelength and half-width of the emission peak of the phosphor refer to values determined by measuring the emission spectrum when irradiated with light having a wavelength of 378 nm. The emission spectrum measurement is performed on a single crystal of the phosphor to be measured. In this specification, the half-width refers to the full width at half maximum (FWHM) and can be determined from the emission spectrum obtained by measuring the emission spectrum when irradiated with light having a wavelength of 378 nm.
[0025] An example of a method for producing a phosphor includes obtaining a fired product from a raw material mixture containing a sodium source, a barium source, silicon dioxide, and europium oxide by one or more firing processes (hereinafter also referred to as a firing step), and heat-treating the fired product in a reducing atmosphere to obtain a heat-treated product (hereinafter also referred to as a reduction step). The heat-treated product may be a target phosphor.
[0026] In the firing step, the raw material mixture is fired to react each raw material component and remove unnecessary components from the raw material components, thereby forming the basic crystal structure of the target phosphor. The firing process in the firing step is preferably performed multiple times, for example, may be performed two or more times, may be performed three or more times, or may be performed three to five times. By performing the firing process multiple times, the proportion of heterogeneous phases in the phosphor can be more sufficiently reduced. One firing process means a series of processes in which the material is heated from room temperature to the target firing temperature, fired at the firing temperature for a predetermined time, and then cooled back to room temperature. When the firing process is repeated multiple times, a crushing process described later may be performed between each firing process.
[0027] In the raw material mixture, the sodium source and the barium source may each independently be a carbonate or an oxide. The sodium source may be, for example, sodium carbonate, etc. The barium source may be, for example, barium carbonate, etc.
[0028] The raw material mixture may contain other components in addition to the sodium source, barium source, silicon dioxide, and europium oxide. Examples of the other components include compounds that melt and form a liquid phase at or below the heating temperature in the firing process. Such compounds function as fluxes, and can promote the reaction of the raw material components and the grain growth of the phosphor particles, thereby producing a more stable phosphor. The compounds that can function as fluxes may be inorganic compounds, and more specifically, magnesium fluoride and the like can be mentioned.
[0029] The raw material mixture can be prepared by weighing and mixing each compound. A dry mixing method or a wet mixing method may be used for mixing. The dry mixing method may be, for example, a method of mixing each component using a V-type mixer or the like. The wet mixing method may be, for example, a method of adding a solvent or dispersion medium such as water to prepare a solution or slurry, mixing each component, and then removing the solvent or dispersion medium.
[0030] The heating temperature (firing temperature) in the firing step may be, for example, 800 to 1200°C, 850 to 1200°C, 900 to 1100°C, or 950 to 1050°C. When the lower limit of the firing temperature is within the above range, the reaction can be further promoted. When the upper limit of the firing temperature is within the above range, the decomposition and volatilization of the raw material components can be further suppressed. When firing is performed multiple times, the firing temperatures for each time may be within the above range, and may be the same or different.
[0031] The heating time (calcination time) in the calcination step may be, for example, 1 to 24 hours, 1 to 20 hours, 1 to 18 hours, 1 to 16 hours, 2 to 15 hours, 2 to 12 hours, 2 to 10 hours, 3 to 10 hours, 5 to 10 hours, or 6 to 9 hours. When the lower limit of the calcination time is within the above range, the reaction can be further promoted. When the upper limit of the calcination time is within the above range, the volatilization of the raw material components can be further suppressed. When the calcination treatment is performed multiple times, the calcination times for each time may be within the above range, and may be the same or different from each other.
[0032] The atmosphere in the firing step (firing atmosphere) may be, for example, air, nitrogen, hydrogen, argon, or a mixture of these gases. The firing atmosphere may be air because the manufacturing process is simple. When firing is performed multiple times, the firing atmosphere for each time may be as described above, but it is preferable that each firing atmosphere is the same as the other firing atmospheres.
[0033] The reduction step is carried out in a reducing atmosphere. By carrying out the reduction step in a reducing atmosphere, europium (Eu), which is an activation element, can be reduced and the valence of the element can be adjusted. More specifically, in the reduction step, Eu 3+ EU 2+ Eu, which contributes to the desired light emission. 2+ The ratio of can be increased. In order to adjust the degree of reduction of the reducing atmosphere, the reducing atmosphere may further contain nitrogen, etc. The reducing atmosphere may be, for example, a mixed gas of nitrogen and hydrogen, or a mixed gas in which nitrogen and hydrogen are mixed at a volume ratio of N2:H2=96:4.
[0034] The heating temperature (reduction temperature) in the reduction step may be, for example, 800 to 1200° C., 900 to 1200° C., 950 to 1150° C., or 100 to 1050° C. When the lower limit of the reduction temperature is within the above range, the reduction efficiency can be improved. Also, when the upper limit of the reduction temperature is within the above range, the decomposition of the fired product can be more sufficiently suppressed.
[0035] The heating time (reduction time) in the reduction step may be, for example, 2 to 15 hours, 4 to 12 hours, 6 to 10 hours, or 7 to 9 hours. When the lower limit of the reduction time is within the above range, the reduction of the activation element can be more sufficient. When the upper limit of the reduction time is within the above range, the decomposition of the fired product can be more sufficiently suppressed.
[0036] The above-mentioned production method may include other steps in addition to the calcination step and the reduction step, such as a crushing step and a classification step.
[0037] The crushing step is a step of crushing the fired product obtained in the firing step and the heat-treated product obtained in the reduction step, which may be obtained in a lump form, and adjusting the particle size. In the crushing step, a mortar or the like may be used, or a general crusher or crusher may be used. Examples of the crusher and crusher include a ball mill, a jet mill, and a Henschel mixer. The crushing step is preferably performed by ball milling in a wet manner in the presence of a medium such as ion-exchanged water. Zirconia balls may be used in the ball mill.
[0038] An example of the light emitting device is a light emitting device including a light emitting element that emits primary light, and a wavelength converter that absorbs a part of the primary light and emits secondary light having a wavelength longer than that of the primary light. The wavelength converter includes the phosphor described above. The light emitting element and the wavelength converter may be sealed with a sealing resin or the like.
[0039] Fig. 1 is a schematic cross-sectional view showing an example of a light emitting device. The light emitting device shown in Fig. 1 is an example of an optical semiconductor device classified as a surface mount type. The light emitting device 100 includes a base material 10, a light emitting element 40 electrically connected to a metal layer 20 provided on the surface of the base material 10, a reflecting section 30 provided on the surface of the base material 10 so as to surround the light emitting element 40, and a transparent sealing resin 60 that fills a recess formed by the base material 10 and the reflecting section 30 and seals the light emitting element 40. A green light emitting phosphor 52 (yellowish green to blue green) and other phosphors 54 are dispersed in the transparent sealing resin 60. The green light emitting phosphor 52 includes the phosphor according to the present disclosure.
[0040] The base material 10 has a metal layer 20 formed on a portion of its surface, and the metal layer 20 serves as an electrode that is electrically connected to a light-emitting element 40 arranged on the surface of the base material 10. The light-emitting element 40 is die-bonded to either the metal layer 20 on the anode side or the cathode side, and is electrically connected to the metal layer 20 via a die-bonding material 42. The light-emitting element 40 is electrically connected to either the metal layer 20 on the anode side or the cathode side via a bonding wire 44.
[0041] The reflecting section 30 is filled with a transparent sealing resin 60 for sealing the light-emitting element 40, and reflects the light (excitation light) emitted from the light-emitting element 40, as well as the fluorescence emitted from the green-emitting phosphor 52 and other phosphors 54 in response to the light, toward the front side of the light-emitting device 100.
[0042] The light-emitting element 40 may emit light (primary light, excitation light) capable of exciting the green-emitting phosphor 52 and the other phosphors 54. The light-emitting element 40 may be, for example, a near-ultraviolet light-emitting diode (near-ultraviolet LED), an ultraviolet light-emitting diode (ultraviolet LED), a blue light-emitting diode (blue LED), or the like. A plurality of light-emitting elements 40 may be provided.
[0043] The light emitting device 100 includes other phosphors 54 in addition to the green-emitting phosphor 52, but may include only the green-emitting phosphor 52. The other phosphors 54 may include, for example, a red phosphor, a yellow phosphor, a blue phosphor, and a green phosphor (a green phosphor other than the phosphor according to the present disclosure), etc.
[0044] In the above example, the light emitting device is described as an optical semiconductor device classified as a surface mount type, but the light emitting device is not limited to this. The light emitting device may be, for example, a light source for analysis, a signal device, or a light source for backlighting a liquid crystal display or liquid crystal panel.
[0045] Although several embodiments have been described above, the present disclosure is not limited to the above-described embodiments. In addition, the descriptions of the above-described embodiments can be mutually applied. EXAMPLES
[0046] The present disclosure will be described in more detail below with reference to examples and comparative examples. However, the present disclosure is not limited to the following examples.
[0047] Example 1 0.17 g of sodium carbonate (Na2CO3, manufactured by Kojundo Chemical Laboratory Co., Ltd.), 2.85 g of barium carbonate (BaCO3, manufactured by Kojundo Chemical Laboratory Co., Ltd.), 1.95 g of silicon dioxide (SiO2, manufactured by Kojundo Chemical Laboratory Co., Ltd.), and 0.03 g of europium oxide (Eu2O3, manufactured by Shin-Etsu Chemical Co., Ltd.) were weighed out and mixed in an alumina mortar in air for 10 minutes to obtain a raw material mixture.
[0048] Next, 5 g of the obtained raw material mixture was placed in an alumina crucible, placed in a vertical furnace, and heated from room temperature to 1000 ° C. at a heating rate of 10 ° C. / min, and held at 1000 ° C. for 8 hours. The atmosphere in the vertical furnace was kept at atmospheric composition. After that, it was cooled to room temperature and crushed in an alumina mortar to obtain a first fired product. The first fired product was fired and crushed under the same conditions as above to obtain a second fired product.
[0049] 4 g of the second fired product obtained as described above was placed in an alumina crucible, and heated in a high-temperature atmosphere furnace from room temperature to 1000°C at a heating rate of 5°C / min, and held at 1000°C for 8 hours. The atmosphere in the high-temperature atmosphere furnace was a mixed gas of nitrogen and hydrogen (mixed so that the volume ratio of N2:H2 was 96:4). After that, it was cooled to room temperature and crushed in an alumina mortar to obtain Na2Ba2O3 having Eu as a solid solution. 9-x S 20 O 50 :EU x A powder of the formula was prepared.
[0050] [Confirmation of crystal structure, and determination of lattice constants and unit cell volume] Crystals were taken from the powder prepared in the examples, and X-ray diffraction measurements were performed using a Bruker single crystal X-ray diffractometer "D8 VENTURE" (product name) to measure the lattice constants a, b, and c of the host crystal. The X-ray diffraction results were analyzed using Bruker single crystal structure analysis software "APEX4" (product name). The unit cell volume was determined from the obtained lattice constants a, b, and c, as well as the values of the axial angles α, β, and γ in the unit cell. The results are shown in Table 1. The obtained lattice constants were used for Na2Ba9Si20 O 50 The lattice constant of the particles obtained in the example is compared with that of Na2Ba9Si 20 O 50 It was confirmed that the compound had the same crystal structure as that of
[0051] [Determination of emission peak wavelength and half-width] Crystals were collected from the powder prepared in the examples, and their emission intensity was measured to confirm whether they functioned as phosphors. Specifically, the collected crystals were first placed on an optical microscope, and the emission spectrum was measured using light with a wavelength of 378 nm as excitation light. A spectrometer "MCPD-9800" (product name) manufactured by Otsuka Electronics Co., Ltd. was used for the measurement. The results are shown in Figure 2.
[0052] Example 2 Except for changing the amount of sodium carbonate to 1.1 times the designed composition, Na2Ba2O3 with Eu as a solid solution was prepared in the same manner as in Example 1. 9-x S 20 O 50 :EU x The crystal structure of the obtained powder was confirmed in the same manner as in Example 1, and it was found to be Na2Ba9Si 20 O 50 It was confirmed that the powder had the same crystal structure as that of the compound obtained in Example 1. It was also confirmed that the powder emitted fluorescence.
[0053] Example 3 Except for changing the amount of sodium carbonate to 1.3 times the designed composition, Na2Ba with Eu solid solution was prepared in the same manner as in Example 1. 9-x S 20 O 50 :EU x The crystal structure of the obtained powder was confirmed in the same manner as in Example 1, and it was found to be Na2Ba9Si 20 O 50 It was confirmed that the powder had the same crystal structure as that of the compound obtained in Example 1. It was also confirmed that the powder emitted fluorescence.
[0054] Example 4 Except for changing the amount of sodium carbonate to 1.5 times the designed composition, Na2Ba with Eu solid solution was prepared in the same manner as in Example 1. 9-x S 20 O 50 :EU x The crystal structure of the obtained powder was confirmed in the same manner as in Example 1, and it was found to be Na2Ba9Si 20 O 50 It was confirmed that the powder had the same crystal structure as that of the compound obtained in Example 1. It was also confirmed that the powder emitted fluorescence.
[0055] [Table 1] [Industrial Applicability]
[0056] According to the present disclosure, a novel phosphor can be provided, which can contribute to expanding design options as the fields in which phosphors are used expand. [Explanation of symbols]
[0057] 10...base material, 20...metal layer, 30...reflective portion, 40...light emitting element, 42...die bond material, 44...bonding wire, 52...green light emitting phosphor, 54...other phosphors, 60...transparent sealing resin, 100...light emitting device.
Claims
1. Na 2 Ba 9 S 20 O 50 A host crystal having the same crystal structure as Eu as an activator element 2+ and
2. 2. The phosphor according to claim 1, which has an emission peak in the wavelength range of 530 to 550 nm in a fluorescence spectrum obtained when irradiated with light having a wavelength of 378 nm.
3. The phosphor according to claim 2 , wherein the half-width of the emission peak is less than 135 nm.
4. General formula Na 2 Ba 9-x S 20 O 50 :Eu x 3. The phosphor according to claim 1, wherein x is a number satisfying 0<x<9.
5. 3. The phosphor according to claim 1, wherein the host crystal is a crystal belonging to a monoclinic system and having space group C12 / m1(12) symmetry.
6. The unit lattice volume calculated from the lattice constant of the host crystal measured by X-ray diffraction is 2.1 to 2.8 nm 3 The phosphor according to claim 1 or 2,
7. The lattice constants a, b, and c of the host crystal measured by X-ray diffraction are respectively a=3.91±0.05nm, b=0.77±0.05nm, c=0.82±0.05nm, The phosphor according to claim 1 or 2,
8. The axial angles α, β, and γ in the unit cell of the host crystal measured by X-ray diffraction are respectively: α=90°、 96°≦β≦98°、 γ=90°, The phosphor according to claim 1 or 2,
Citation Information
Patent Citations
Wavelength conversion material and solar cell module using the same
JP2019215451A
Phosphor, method for producing same, light emitting element and light emitting device
WO2022244523A1